Surface Treatment of Areca-Nut Fiber Using Silane and Gamma Irradiation: Fabrication of Polycaprolactone Based Composite - Dey, Kamol; Ganguly, Sumon; Khan, Ruhul A.; Khan, Mubarak A. (Journal of Composites and Biodegradable Polymers, 2013)
Composite materials enjoy great attraction in material science. The objective of this research was to fabricate natural fiber reinforced polymer matrix composites and to increase performances through physical and chemical methods. Areca nut fiber (50 % by weight) reinforced polycaprolactone (PCL) based unidirectional composites were prepared by compression molding. Tensile strength (TS), tensile modulus (TM), bending strength (BS), bending modulus (BM) and impact strength (IS) of the composite were found to be 32 MPa, 685 MPa, 45 MPa, 820 MPa and 15 kJ/m2, respectively.Six different formulations (F1-F6) of vinyl trimethoxy silane (VTMS) (1-6wt%) along with methanol (97-92%) and photo-initiator Darocur-1173 (2%) were prepared in order to modify the surface of areca nut fiber. Areca nut fiber were soaked for 15 min in different formulations and then exposed under gamma radiation of various doses (250-1000 krad). Composite made of areca nut fiber treated with 4% silane and at 500 krad dose of gamma radiation performed the highest mechanical properties. TS, BS, TM, BM and IS of the composite were found to be 43 MPa, 64 MPa, 1015 MPa, 1423 MPa and 20 kJ/m2, respectively. Polymer loading (PL) of the gamma treated and untreated fiber was studied. Degradation test of the composites was carried out for 6 weeks in soil medium and it was found that the treated composite retained much of its original strength. It can be concluded that silane and gamma radiation are important tools to improve the mechanical property of the composite.